Clinical Impact of Subsequent Depression in Patients With a New Diagnosis of Stable Angina: A Population-Based Study. (November 2016) - Szpakowski, Natalie; Bennell, Maria C.; Qiu, Feng; Ko, Dennis T.; Tu, Jack V.; Kurdyak, Paul; Wijeysundera, Harindra C.
Abstract : Background—: Depression is prevalent among patients with myocardial infarction and is associated with a worse prognosis. However, little is known about its importance in patients with chronic stable angina. We conducted a retrospective population-based cohort study to determine the occurrence and predictors of developing depression in patients with a new diagnosis of chronic stable angina. In addition, we sought to understand its impact on subsequent clinical outcomes. Methods and Results—: Our cohort included patients in Ontario, Canada, with stable angina based on obstructive coronary artery disease found on angiogram. Depression was ascertained by physician billing codes and hospital admissions diagnostic codes. We first developed multivariable Cox proportional hazards models to determine predictors of developing depression. Clinical outcomes of interest included all-cause mortality, admission for myocardial infarction, and subsequent revascularization. Using hierarchical multivariable Cox proportional hazards models with occurrence of depression as a time-varying variable to control for potential immortal time bias, we evaluated the impact of depression on clinical outcomes. Our cohort consisted of 22 917 patients. The occurrence of depression after diagnosis of stable chronic angina was 18.8% over a mean follow-up of 1084 days. Predictors of depression included remote history of depression, female sex, and more symptomatic angina based on Canadian Cardiovascular Society class. Patients who developed depression had a higher risk of death (hazard ratio 1.83, 95% confidence interval 1.62–2.07) and admission for myocardial infarction (hazard ratio 1.36, 95% confidence interval 1.10–1.67) compared with nondepressed patients. Conclusions—: Depression is common in patients with chronic stable angina and is associated with increased morbidity and mortality. Abstract : Supplemental Digital Content is available in the text.